Pengaruh Peran Pemerintah Desa Terhadap Pemberdayaan Kelompok Tani Di Desa Ollot Kecamatan Bolangitang Barat Kabupaten Bolaang Mongondow Utara - Della Puspita Sari Labindjang; Mochammad Sakir; Purwanto Purwanto; Hasan Bau (Program Studi Ilmu Pemerintahan, 2026)
Empowering farmer groups is an important strategy in increasing the capacity and independence of farmers at the village level. The role of the village government is a factor suspected to be influential in supporting the empowerment process through guidance, facilitation, and institutional strengthening. This study aims to analyze the influence of the village government's role on the empowerment of farmer groups in Ollot Village, West Bolangitang District, North Bolaang Mongondow Regency. The study used a survey method with a quantitative approach. The research sample consisted of 41 respondents selected from farmer group members. The data analysis technique used simple linear regression to test the magnitude of the influence of independent variables on the dependent variable. The results showed that the role of the village government had a positive effect on the empowerment of farmer groups with a coefficient of determination (R²) of 0.677. This value indicates that 67.7% of the variation in farmer group empowerment can be explained by the role of the village government, while the remaining 32.3% is influenced by other factors outside the research model. These findings indicate that the role of the village government has a strong contribution in increasing the empowerment of farmer groups. Therefore, the village government's coaching, mentoring, and facilitation functions need to be continuously optimized to strengthen the independence and capacity of farmer groups in a sustainable manner.